(untitled) (African Journal of Biomedical Research, 2024)
This study examined Ghanaian veterinary and medical students’ knowledge and perception of zoonoses’ public health impact. The cross-sectional survey and online structured questionnaire were completed by 384 students (174 veterinary and 210 medical students) from 4 Ghanaian state universities. SPSS version 25 was used to descriptively evaluate data using mean scores, Pearson Chi-square, and regression analysis. The study found that 78.6% of medical and veterinary students in Ghana have decent understanding of zoonoses, with a mean response of 4.88 ± 1.049. Veterinary students (42.9%) knew more about zoonosis than medical students (35.7%). 83.6% of medical and veterinary students had a strong opinion of the public health importance of zoonoses, with a mean of 3.99 ± 1.017. Medical students (45.8%) had a higher view of zoonosis than veterinary students (37.8%). Students’ awareness of zoonosis was not substantially associated to religion (P=0.694) or institution (P=0.06), but was significantly related to gender (P=0.044), school (P=0.031), and year of study (P=0.004). Students’ perceptions of zoonoses’ public health significance were not significantly related to gender, religion, institution, or school (P>0.05), but were significantly related to their year of study (P<0.001). Ghanaian medical and veterinary students had strong awareness and perceived public health importance of zoonoses, especially clinical students. Policy debate is needed to evaluate medical and veterinary pre-clinical education to include zoonoses. To understand their role in zoonoses control, medical, veterinary, animal, and environmental science students should attend workshops.